8 Drivers and potential solutions for overdiagnosis: perspectives from the low and middle income countries. (4th December 2019) - Pathirana, Thanya; Wang Yu, Matthew; Martiny, Frederik; Rupasinghe, Maithri; Kottahachchi, Dulani; Wijewickrama, Ananda; Copp, Tessa; Kumar, Raman; Mendis, Kumara
Abstract : The issue of too much medicine and overdiagnosis has drawn considerable attention in the high-income countries. However, in the low-income and low-middle income countries (LMIC) where the problem is equally, if not more rampant, it has not come to attention. Although the undersupply and inaccessibility of healthcare remain major problems in most of these countries, the emerging issue of overdiagnosis threatens health systems, health financing and health equity, and cannot be neglected. Preventing Overdiagnosis Conference, first organized in 2013, has become a strong international platform which brings together a wide range of stake holders working on preventing overdiagnosis - although to date, the focus has been more on the developed countries. In 2019, with the conference being held for the first time in the Asia Pacific region, we aim to bring more attention to the key drivers of overdiagnosis and possible solutions in LMICs, which may be very different from high-income countries. In this workshop, we attempt to 1. Better understand the issue of over-diagnosis in LMICs 2. Identify and describe the possible drivers and potential solutions for overdiagnosis in LMIC. 3. Explore opportunities for collaborations with developed countries and other international stakeholders working on preventing overdiagnosis In the LMICs, patients' expectations for a rapid recovery, doctor shopping, less onus with life-style modification and lack of follow-up in primary care, play a vital role in overtesting and overtreatment. Thus, the overarching cultural norms of 'more is better', 'quicker is better' in a background of lack of knowledge and awareness about the negative effects of overdiagnosis only add to the epidemic of it. Compared to high-income countries, fear of litigation plays minimal (if any) role. The doctors who practice medicine primarily as a business commonly receive undeclared industry sponsored financial and other incentives for laboratory tests and treatment. These practices are invigorated by the lack of local evidence-based guidelines (e.g. breast cancer screening, prescribing antivirals/antibiotics, cut-offs for hypertension, diabetes, ordering CT/MRI) and quality control measures for laboratory results. The medical education system in the region is based on the western/allopathic system with emphasis on secondary and tertiary care, which places too much emphasis on 'diagnosis/labelling' and treatments. Most of the medical graduates have limited skills in primary care, and lack specific skills dealing with tolerance and uncertainty. To address these complex and multifaceted drivers we propose focused awareness campaigns for health professionals as well as the public. In addition, generating point of care evidence-based guidelines and introducing shared decision making to the patient management process will be novel but important strategies for our region. Ensuring comprehensive evaluation prior to introduction of new tests will help in reducing the negative effects of overdiagnosis, associated overtreatment and overuse. These strategies may support maintaining sustainability of resource poor health systems in the region. Proposed agenda: Introduction to the topic; Presentations by invited health professionals from China, India, Sri Lanka and an eastern European country – focusing on current status of this issue and strategies proposed/undertaken to address it in their countries; Small Group discussion – To discuss the drivers and solutions for overdiagnosis in LMIC; Panel discussion with the speakers, and invited experts from high income countries and international organizations – The ideas generated from the group discussions will be shared with the audience. The panel discussion will focus on these as well as explore opportunities for collaborations with developed countries and other international stakeholders working on preventing overdiagnosis; Conclusion.